A system of national accounts - United Nations (New York: United Nations, 1968)
This report presents the new System of National Accounts (SNA) which the fifteenth session of the Statistical Commission adopted for the use of national statistical authorities and in the international reporting of comparable national accounting data.
"United Nations publication. Sales no.: E.69. XVII. C3."
1953 and 1964 editions published under title: A system of national accounts and supporting tables.
osa; 03/10/17
Loans
Keywords: National income